IMPLEMENTATION OF THE PROJECT APPROACH TO MANAGEMENT OF TOURISM DEVELOPMENT OF THE REGION - Kinash, Iryna Petrivna; Stavnycha, Nataliia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article focuses on the specifics of project implementation in the region. The purpose of the article is to reveal the relevance of the project approach to the development of tourism and research the progress of the implementation of tourism projects in the selected region. Attention is focused on negative trends in the development of tourism in Ukraine. Their reasons were: financial and economic crisis; events related to the annexation of the Autonomous Republic of Crimea and the conduct of an anti-terrorist operation on the territory of Donetsk and Luhansk regions; the COVID-19 pandemic; full-scale Russian invasion of Ukraine. The Ivano-Frankivsk region was chosen as the object of the study. It is the leader of domestic tourism in Ukraine (visited by 2 million tourists and sightseers every year). Factors that indicate a significant potential for tourism development in this region are substantiated. They are: favorable natural and climatic conditions, availability of a significant amount of natural and cultural resources, well-developed tourist infrastructure, preserved national traditions and folklore. Trends in the development of tourism in the region during 2019-2021 were studied. It was found that the potential of the tourism sector is not being used properly. The reasons and their nature are outlined. For the successful use of the existing tourist potential, it is proposed to apply a project approach. The classification of projects is presented. The main tourist projects implemented in the region today are considered. Their purpose, performers, partners, duration, and budget are described. It was found that in total, in 2022, more than ten international grant projects were implemented in the Ivano-Frankivsk region. It has been studied that the main majority of them are aimed at the development of cross-border tourism. The tasks aimed at such tourism are presented. It was concluded that the situation taking place in Ukraine today creates conditions for intensive planning of the development of various branches of the economy, including the field of tourism. It is the project approach, in our opinion, that is an effective tool for regional socio-economic development, which enables the rational use of tourism potential.